2000
DOI: 10.1055/s-2000-14508
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy with Ultrasonic Contact Microprobe

Abstract: The authors describe their first clinical experiences in endoscopic third ventriculostomy (ETV) with the original ultrasonic contact microprobe (UCM) designed at the Department of Neurosurgery in Zagreb. The analysis includes the clinical course of disease in eight patients submitted to surgery from May to September 1999 (3 men and 5 women, from 14 to 61 years of age). Surgery was performed in patients with neurological symptoms of elevated intracranial pressure and neuroradiological evidence of non-communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…14 Localization of the basilar complex and the relationship to the floor of the third ventricle was considered quite reliable. Paladino et al 19 used an ultrasonic contact microprobe to perforate the floor of the third ventricle and serve as a guide to avoid the basilar complex simultaneously. The perforation was then widened by balloon dilation.…”
Section: Management Of the Ventricle Floor In Etvmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Localization of the basilar complex and the relationship to the floor of the third ventricle was considered quite reliable. Paladino et al 19 used an ultrasonic contact microprobe to perforate the floor of the third ventricle and serve as a guide to avoid the basilar complex simultaneously. The perforation was then widened by balloon dilation.…”
Section: Management Of the Ventricle Floor In Etvmentioning
confidence: 99%
“…Some have considered an opaque floor, on occasion, to be a contraindication to proceeding with an ETV. 12,29 Methods used in attempting to deal with the opaque floor have included balloon tip dilation/dissection, 2,21 thermal monopolar technique, 23 use of an ultrasonic contact probe, 19 bipolar coagulation, 25,26 laser penetration, 23,32 water jet irrigation, 2,18 use of spreading forceps, 33 ultrasonography, 14 Doppler detection of the BA complex, 24 and blind probing with a blunt instrument. 1,2,9,16 Grotenhuis designed a special endoscopic perforator to draw up the floor of the third ventricle away from the BA complex as it cuts through the floor of the third ventricle.…”
mentioning
confidence: 99%
“…These probes o¤er the major advantage of direct visualization of the anatomical structures of the interpeduncolar and prepontine cisterns and can be used for blunt perforation of the floor. This allows safer perforation under the double control of the floor of the third ventricle (endoscopic) and of the anatomical and vascular structures hidden behind the floor membrane (ultrasonographic) (Paladino et al 2000, Resch and Reisch 1997, Resch and Perneczky 1998, Resch 2003 (Fig. 18a-c).…”
Section: Ultrasound Microprobesmentioning
confidence: 99%
“…The rate of significant complications ranges around 7% of the cases with only one sixth of them leading to permanent neurological damages (Broggi et al 2000, Fukuhara et al 2000, Sainte-Rose and Chumas 1996, Schroeder et al 2002, Teo et al 1991. Many of these complications, often the most severe ones, occur during the opening of the floor of the third ventricle, a phenomenon which accounts for a large number of techniques and instruments proposed so far to carry out the ventriculocisternostomy (Decq et al 2004, Guiot 1973, Kehler et al 1998, Kunz et al 1994, Lewis and Crone 1994, Oka et al 1993b, Paladino et al 2000, Rieger et al 1996, Vandertop et al 1998, Vries 1978, Wellons et al 1999). On the other hand, non-significant complications are linked up to transient intra-operative accidents (small bleeding, least contusions of the ventricular wall or the brain, short episodes of bradycardia) that do not affect the success of the operation and do not cause any significant damages.…”
Section: Complicationsmentioning
confidence: 99%
“…LTHOUGH various instruments have been used for dissection in neuroendoscopic surgery, including high-frequency current (using monopolar or bipolar electrodes), 26 thermal lasers, 7 ultrasonic probes, 20,21,27 and mechanical dissection techniques, 4 it is still difficult to perform controlled dissection without causing bleeding and thermal damage in surrounding tissue. 2,11 Over the past two decades waterjet dissection has been introduced into medical use, 22 and various experiments and in vivo studies have demonstrated its superiority over conventional dissection devices.…”
mentioning
confidence: 99%